PENGARUH MASA KERJA, OPENNESS TO EXPERIENCE DAN DIGITAL MINDSET TERHADAP READINESS FOR CHANGE PADA GURU - Mardianti Mardianti; Wahyu Rahardjo (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Digital transformation in schools requires teachers to be ready for change; however, studies that integrate tenure, openness to experience, and digital mindset in explaining teachers’ readiness for change remain limited. This study aimed to examine the effects of tenure, openness to experience, and digital mindset on teachers’ readiness for change. This quantitative study involved 127 teachers in Jakarta selected using convenience sampling. Data were collected using the Readiness for Change Scale, the openness to experience scale from the Indonesian version of the Big Five Inventory, and the Digital Mindset Scale. The data were analyzed using multiple regression. The results showed that tenure, openness to experience, and digital mindset simultaneously contributed to teachers’ readiness for change. Partially, tenure was negatively associated with readiness for change, whereas openness to experience and digital mindset were positively associated with readiness for change. These findings indicate that teachers’ readiness for change is not only related to work experience but also to openness to new experiences and a digital-oriented mindset. This study highlights the importance of developing openness to experience and digital mindset to support teachers’ readiness to face technology-driven educational change. ABSTRACT Transformasi digital di sekolah menuntut guru memiliki kesiapan untuk menghadapi perubahan, tetapi kajian yang mengintegrasikan masa kerja, openness to experience, dan digital mindset dalam menjelaskan readiness for change pada guru masih terbatas. Penelitian ini bertujuan untuk menguji pengaruh masa kerja, openness to experience, dan digital mindset terhadap readiness for change pada guru. Penelitian kuantitatif ini melibatkan 127 guru di Jakarta yang dipilih menggunakan teknik convenience sampling. Data dikumpulkan menggunakan Skala Readiness for Change, skala openness to experience dari Big Five Inventory versi Indonesia, dan Skala Digital Mindset. Data dianalisis menggunakan regresi ganda. Hasil penelitian menunjukkan bahwa masa kerja, openness to experience, dan digital mindset secara simultan berkontribusi terhadap readiness for change pada guru. Secara parsial, masa kerja berkaitan negatif dengan readiness for change, sedangkan openness to experience dan digital mindset berkaitan positif dengan readiness for change. Temuan ini menunjukkan bahwa kesiapan guru dalam menghadapi perubahan tidak hanya berkaitan dengan pengalaman kerja, tetapi juga dengan keterbukaan terhadap pengalaman baru dan pola pikir digital. Penelitian ini menegaskan pentingnya pengembangan openness to experience dan digital mindset untuk mendukung kesiapan guru menghadapi perubahan pendidikan berbasis teknologi.